REVITALISASI KAWASAN PERMUKIMAN PADA AKTIFITAS PEREKONOMIAN MASYARAKAT DI BANTARAN SUNGAI PALU - Arisani, Ratna Eka (Katalogis, 2017)
This research aims to find out the effort that made to revitalize of settlement area in riverbanks Palu and find out the public response on implementation of the revitalization. Type of research was qualitative, while the method used survey. The research show that implementation of the revitalization of the settlement riverbanks Palu area can have a positive impact on public economic with the space of economic activity.